The benefits of physical activity in men with prostate cancer-a systematic review - Boing L.* (2016)
This is a systematic review whose objective was to analyze original studies investigating the association of physical activity in the health of men diagnosed with prostate cancer. The databases used were PubMed, Web of Science, Science Direct, Virtual Library Scielo, and Virtual Library of Health. The descriptors used in the search were [physical activity] AND [prostate cancer] in English, Spanish and Portuguese. We included 21 studies published in English, from 2004 to 2015. The investigations had increased focus on physical activity and other variables, relating positively to improving the quality of life. Positive results were observed in the physical, fatigue and sexual function in addition to the decrease in waist circumference and blood pressure. Further studies are suggested in order to investigate the physical activity at different intensities with longitudinal methodologies, permeating the diagnosis, the treatment period and recovery.